Relationship between the vertical distribution of fine roots and residual soil nitrogen along a gradient of hardwood mixture in a conifer plantation. Issue 3 (8th June 2022) - Morikawa, Yumena; Hayashi, Seiji; Negishi, Yuki; Masuda, Chie; Watanabe, Mirai; Watanabe, Keiji; Masaka, Kazuhiko; Matsuo, Ayumu; Suzuki, Masanori; Tada, Chika; Seiwa, Kenji
Summary: In forest ecosystems, understanding the relationship between the vertical distribution of fine roots and residual soil nitrogen is essential for clarifying the diversity–productivity–water purification relationship. Vertical distributions of fine‐root biomass (FRB) and concentrations of nitrate‐nitrogen (NO3 ‐N) in soil water were investigated in a conifer plantation with three thinning intensities (Control, Weak and Intensive), in which hardwood abundance and diversity were low, moderate and high, respectively. Intensive thinning led to the lowest NO3 ‐N concentration in soil water at all depths (0–100 cm) and highest FRB at shallow depths (0–50 cm). The NO3 ‐N concentration at a given depth was negatively correlated with total FRB from the surface to the depth at which NO3 ‐N concentration was measured, especially at shallow depths, indicating that more abundant fine roots led to lower levels of downward NO3 ‐N leaching. FRB contributed positively to nitrogen content of hardwood leaves. These findings demonstrate that a hardwood mixture in conifer plantations resulted in sufficient uptake of NO3 ‐N from soil by well developed fine‐root systems, and translocation to canopy foliage. This study suggests that productivity and water purification can be achieved through a hardwood mixture in conifer plantations.